O Impacto da gestação na função dos músculos do assoalho pélvico de primigestas - Palmezoni, Vanessa Pinho (2016)
The pelvic floor muscles (PFM) are responsible for supporting the pelvic viscera and for promote urinary and fecal continence. Several studies observed the consequences of the perineal trauma during childbirth on the PFM, but there is lack of research in order to evaluate these muscles during pregnancy, so, although the physiological changes of pregnancy is known, there is not enough data on how these changes influence the PFM function. Therefore, this study aims to evaluate the functions of PFM during pregnancy and compare with nulliparous pelvic floor (PF) function. It is a cross-sectional study, observational, comparative, conducted between April and July 2015.The study population consisted of 141 women: 36 nulliparous (C group), 31 primiparous on first trimester pregnancy (1T group), 42 on second trimester (2T group) and 32 on third (3T group). The PF was evaluate by measuring the size of the genital hiatus (HG) and the perineal body (CP) and measuring the strength of the muscles through the bi-digital palpation (Pb), perineometry (Pe) and dynamometry (Din). The Levene test was used to check homogeneity of the samples regarding age, the Kruskal-Wallis test (ANOVA non-parametric) was applied on the variables to assess significant differences in the groups (C, 1T, 2T and 3T) and U test of Mann-Whitney for paired comparison. For correlation of the variables, we calculated the correlation coefficient by Spearman\'s Rank. The level of significance was establish at 0.05. Regarding the HG and CP variables, when comparing the groups, the lowest values were observed in C group (HG = 1.75cm and CP = 2.5cm) and increased in 3T group (HG = 2.25 cm and CP = 3, 5cm). Concerning the strength variables (Pb, Pe and Din) the initial study hypothesis was confirmed, with the group of nulliparous higher (Pb = 3.2; Pe = 45.6 cmH2O and Din = 1.2 kgf) of strength compared to the third trimester primiparous group (Pb = 2.1; Pe = 17.3 cmH2O and Din = 0.7 kgf). The correlation between the HG, CP and the strength measurements, demonstrated that the variable HG was not found and the CP was negatively correlated with Pe and Din (r = - 0.219 and r = - 0.228). Already comparing Pb variables, Pe and Din, it was possible to establish a positive correlation (Pb x Pe (r = 0.757); Pe x Din (r = 0.755) and Pb x Din (r = 0.564). For variables HG and CP, the highest numbers in 3T group were expected due to changes during pregnancy. The highest values for Pb, Pe and Din found in C group can also be explained when compared to lower values in 3T group, also for sustained changes by pregnant women. The positive correlation between the strength of assessment methods (Pb, Pe and Din) proven by this study, strengthened our results and concluded that there is a significant difference in PFM strength between primiparous on third trimester of pregnancy and nulliparous, suggesting pregnancy as a risk factor for reduction of the PFM strength.